Increasing tax transparency: Investor reactions to the country-by-country reporting requirement for EU financial institutions - Verena Dutt; Christopher A. Ludwig; Katharina Nicolay; Heiko Vay; Johannes Voget (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2018)
We employ an event study methodology to investigate the stock price reaction around the day of the political decision to include a country-by-country reporting obligation for EU financial institutions. We do not find significant abnormal returns for the banks affected. Sample splits according to the effective tax rate and the degree of B2C orientation do not reveal a more pronounced negative investor response for banks engaging more strongly in tax avoidance or being potentially more concerned about reputational risks, respectively. We conclude that the implementation of a CbCR requirement for EU financial institutions did not trigger a noticeable investor response. Contrary prior findings regarding other public tax disclosure obligations might be driven by the distinct motivation of the rules and the way the information is presented. We contend that capital market reactions to an upcoming increase in tax transparency are not generalizable to other industries and settings, but that consideration must be given to the context and the exact design of the rule.
urn:nbn:de:bsz:180-madoc-456641
Keywords: H25; H26; G21; G28; 330; Tax Avoidance; Profit Shifting; Country-by-Country Reporting; Financial Institutions; Market Reaction